The Influence of Third-Party Funds, Financing-to-Deposit Ratio, and Non-Performing Financing on Financing at PT Bank Muamalat with Total Assets as an Intervening Variable - Marlis Tanjung, Ami Nullah (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to examine and analyze the relationships betweenThird-Party Funds and both Financing and Total Assets,Non-Performing Financing (NPF) and both Financing and Total Assets, and Financing-to-Deposit Ratio (FDR) and Financing at Bank Muamalat during the 2016-2020 research period.The research employs time-series secondary data collected from quarterly financial reports published by Bank Muamalat. Analytical methods include Descriptive Analysis, Classical Assumption Testing, and Path Analysis utilizing LISREL software version 8.8.At a 5% significance level, the path analysis results reveal several key findings: First, Third-Party Funds significantly affect the intervening variable of Total Assets, while Non-Performing Financing shows no significant impact on Total Assets. Second, both Third-Party Funds and Financing-to-Deposit Ratio demonstrate significant influence on Financing. Conversely, neither Total Assets nor Non-Performing Financing exhibit significant effects on Financing at Bank Muamalat during the study period.Keywords : Third Party Funds, Non Performing Financing,Financing of Deposit Ratio, Total Assets and Financing